PREGNANCY RATE AFTER OVULATION INDUCTION, SPERM INTRAUTERINE TRANSFER (SIUT) AND LUTEAL SUPPORT THERAPY IN LUTEAL PHASE DEFECT (LPD) INFERTILE PATIENTS. - Albarzanhi, Mundhir R.; Al-Anssari, saada; mahmoud, Suhair nadim; taiyeb, ahmed (Journal of the Faculty of Medicine Baghdad, 2005)
Summary: Background: It is well known that the early removal of corpus luteum (CL) in pregnant women results in abortion . Defects in the function of CL lead to deficiency in the secretion of progesterone which adversely affect human embryo implantation . Aim of the work: l)to determine progesterone concentration in the luteal phase defect (LPD) patients complaining from infertility and 2) to evaluate the clinical value of ovulation induction, sperm intrauterine insemination SIUT and luteal support therapy in the treatment of LPD patients. Patients & Methods: One hundred and twelve LPD patients were involved in this study. The progesterone concentrations were performed by radioimmunoassay method on cycle day 21. Patients were considered to have severe LPD when progesterone concentration was 3.56 ng/ml and mild LPD when the progesterone concentration was less than 8.63 ng/ml. Those patients who had progesterone concentration of more than 10 ng/ml were considered normal (without LPD). Ovulation induction was induced by clomiphene citrate (lOOmg/day for five days) and human menopausal gonadotropin (300 international units for another five days) and human chorionic gonadotropin (HCG) treatments. Standard technique for in vitro activation of human sperm and sperm intrauterine insemination (SIUI) were performed. Following III I the patients were received 1500 IU of HCG on cycle day 14,17,20 and 23. Results: The pregnancy rate in the severe LPD group was significantly lower (P<0.05) than that of control and mild LPD groups. The pregnancy rate in the control (without LPD) and mild LPD group was significantly not different (P>0.05). This indicates that the outcome of luteal support therapy following ovulation induction and SIUT was significantly improved when compared to control group .